2019
DOI: 10.3390/ijms20215497
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Formation of Ag Nanoparticles in Mesoporous TiO2 Films Decorated on Bamboo via Self-Sacrificing Reduction to Synthesize Nanocomposites with Efficient Antifungal Activity

Abstract: We developed a novel green approach for the in situ fabrication of Ag NPs in mesoporous TiO2 films via the bamboo self-sacrificing reduction of Ag(NH3)2+ ions, which can inhibit fungal growth on the bamboo surface. Mesoporous anatase TiO2 (MT) films were first synthesized on bamboo via a hydrothermal method. Then, Ag NPs with a 5.3 nm mean diameter were incorporated into the pore channels of optimal MT/bamboo (MTB) samples at room temperature without the addition of reducing agents, such that the Ag NPs were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 43 publications
0
12
1
2
Order By: Relevance
“…These results indicate that the AB samples had poor resistance to A. niger. Our previous work similarly showed that nanosized Ag-treated bamboo samples have poor resistance to P. citrinum and T. viride [35]. In addition, we did not observe any Our previous work similarly showed that nanosized Ag-treated bamboo samples have poor resistance to P. citrinum and T. viride [35].…”
Section: Inhibition Of a Niger Spores In Darknesscontrasting
confidence: 47%
See 2 more Smart Citations
“…These results indicate that the AB samples had poor resistance to A. niger. Our previous work similarly showed that nanosized Ag-treated bamboo samples have poor resistance to P. citrinum and T. viride [35]. In addition, we did not observe any Our previous work similarly showed that nanosized Ag-treated bamboo samples have poor resistance to P. citrinum and T. viride [35].…”
Section: Inhibition Of a Niger Spores In Darknesscontrasting
confidence: 47%
“…Our previous work similarly showed that nanosized Ag-treated bamboo samples have poor resistance to P. citrinum and T. viride [35]. In addition, we did not observe any Our previous work similarly showed that nanosized Ag-treated bamboo samples have poor resistance to P. citrinum and T. viride [35]. In addition, we did not observe any mycelial growth on the surfaces of the TB, ATB-5, ATB-10, ATB-30, and ATB-200 samples after incubation for five days.…”
Section: Inhibition Of a Niger Spores In Darknessmentioning
confidence: 77%
See 1 more Smart Citation
“…In addition, organic fungicides are always toxic and harmful to humans and livestock. Recently, a number of studies have developed novel inorganic mildew preventives with lower toxicity, including nano-ZnO [ 14 , 15 , 16 ], TiO 2 [ 17 , 18 , 19 ], CuO [ 20 ], graphene [ 21 ], Ag, or a combination of them [ 22 , 23 , 24 , 25 ]. These nano-sized inorganics form a protective coating layer at wooden products surface.…”
Section: Introductionmentioning
confidence: 99%
“…Mori et al evaluated the antibacterial and cytotoxicity properties of silver nanowires and their composites with carbon nanotubes for biomedical applications [ 36 ]. Li et al reported a simple, sustainable, and environmentally friendly method for the in situ fabrication of silver nanoparticles in mesoporous TiO 2 films decorated on bamboo via self-sacrificing reduction to synthesize nanocomposites with an efficient antifungal activity [ 37 ]. The composite films-endowed bamboo exhibited an excellent antifungal activity to T. viride and P. citrinum.…”
mentioning
confidence: 99%